Linking eco-innovation and circular economy: A conceptual approach - Magdalena Pichlak; Adam R. Szromek (Journal of Open Innovation: Technology, Market, and Complexity, 2022)
The socio-economic transformations taking place nowadays bring about the necessity to transform the currently dominating linear paradigm of economic growth. The basis for such a transformation is, first of all, the implementation of sustainable systems of production and consumption, so that they evolve into companies implementing the assumptions of a closed-circle economy. Although the concept of such an economy has been widely accepted by both researchers and practitioners, there is still a lack of thorough recognition of the determinants of its application at the organizational level. Attempting to fill this research gap, this paper addresses the conceptual link between companies' eco-innovation activities and the CE paradigm. It attempts to assess the importance of eco-innovation, both technological and nontechnological in nature, as determinants of the implementation of the concept of a closed-loop economy. The prospects for the implementation of a closed-loop economy are described, then the concepts and types of eco-innovation are organized, and finally the role of eco-innovation as a catalyst for the implementation of the CE concept is explained. The article also indicates the most important management practices, understood as strategic actions necessary in the process of generating and implementing innovations leading to the realization of the idea of reverse material flows. As a consequence of the discussion, the proposition suggested herein is to develop the existing circular business models by taking into account the eco-innovative activities of enterprises. The article is also an attempt to start a discussion on the category of open eco-innovations and to popularize the practice of open access to eco-innovations.
Keywords: 650; business model; circular business model; circular economy; eco-innovation; open eco-innovation; open innovation